Precise Editing of chNHE1 Gene via CRISPR/Cas9 Generates ALV-J-Resistant Chicken Primordial Germ Cell - Xinyi Zhou; Ruyu Liao; Min Tan; Yu Zhang; Haiwei Wang; Keshan Zhang; Qigui Wang; Xi Lan (Animals, 2025)
Avian leukosis virus subgroup J (ALV-J), an α-retrovirus, mediates infection by binding to the host-specific receptor chNHE1 (chicken sodium–hydrogen exchanger type 1), leading to immunosuppression and tumorigenesis, which severely threatens the sustainable development of the poultry industry. Studies have shown that the tryptophan residue at position 38 (W38) of the chNHE1 protein is the critical site for ALV-J infection. In this study, we employed the CRISPR/Cas9 system to construct a lentiviral vector targeting the W38 site of chNHE1, transfected it into chicken primordial germ cells (PGCs), and validated its antiviral efficacy through ALV-J infection assays, successfully establishing an in vitro gene-editing system for chicken PGCs. The constructed dual lentiviral vector efficiently targeted the W38 site. PGCs isolated from 5.5- to 7-day-old chicken embryos were suitable for in vitro gene editing. Stable fluorescence expression was observed within 24–72 h post-transfection, confirming high transfection efficiency. ALV-J challenge tests demonstrated that no viral env gene expression was detected in transfected PGCs at 48 h or 72 h post-infection, while high env expression was observed in control groups. After 7 days of infection, p27 antigen ELISA tests were negative in transfected groups but positive in controls, indicating that W38-deleted PGCs exhibited strong resistance to ALV-J. This study successfully generated ALV-J-resistant gene-edited PGCs using CRISPR/Cas9 technology, providing a novel strategy for disease-resistant poultry breeding and advancing avian gene-editing applications.